Effect of Pupil Size and Binocular Viewing on Accommodative Gain in Emmetropia and Myopia. Issue 3 (2nd July 2020) - Huang, Chun Tang; Satou, Tsukasa; Niida, Takahiro
ABSTRACT: Purpose: To evaluate the differences in accommodative gain in response to different accommodative stimuli and determine the effects of pupil size, binocular viewing, and inherent eye refraction on accommodative gain. Methods: This study enrolled 47 healthy young adults (emmetropia: 21 eyes, myopia: 26 eyes). Refractive value and pupil size during accommodative stimulus were measured using an open-viewing type auto-refractor (Grand Seiko WAM-5500). The subject was continuously presented with six stimuli (0D, 1D, 2D, 3D, 4D, and 5D) in front of the eye. Measurements were performed under three conditions. Condition 1: Monocular status with complete occlusion of the non-viewing eye; Condition 2: Monocular status with occlusion of the non-viewing eye by translucent occluder; Condition 3: Binocular status. Results: In the emmetropia group, there was no significant difference in accommodative gain between conditions 1 and 2 ( p > .05), but conditions 2 and 3 were significantly different ( p < .05). In the myopia group, accommodative gain was significantly different between conditions 1 and 2 with stimuli 3D, 4D, and 5D ( p < .05), but conditions 2 and 3 were not significantly different ( p > .05). Conclusions: The effects of pupil size and binocular viewing on accommodative gain differed between emmetropia and myopia.